MODEL PEMBELAJARAN KOOPERATIF TIPE STAD, CARA BELAJAR DAN MOTIVASI BELAJAR KAITANNYA TERHADAP SIKAP BEREKONOMI PADA SISWA SMP - Munawaroh, (Pendidikan Ekonomi, 2010)
This research is intended to: 1) clarify the influence of cooperative learning of STAD type towards the students economic behavior; 2) clarify the influence of learning ways towards the students economic behavior; 3) clarify the influence of learning motivation towards the students economic behavior; 4) clarify the influence of cooperative learning of  STAD type towards learning ways; 5) clarify the influence of learning ways towards learning motivation; 6) clarify the influence of cooperative learning of  STAD type towards learning motivation; 7) clarify the influence of cooperative learning of STAD type, learning ways, and learning motivation towards the economic behavior of the students of SMP Negeri 5 Jombang. The research is designed to be a quasi experiment where 362 students of SMP Negeri 5 Jombang as the population. the samples that are randomly assigned. Then the data gathered are analyzed using ANOVA, simple and multiple linear regressions. To calculate the data, the researcher used statistical application of SPSS For windows 13 version.